2006
DOI: 10.1177/1934578x0600100613
|View full text |Cite
|
Sign up to set email alerts
|

Some Biological Properties of Curcumin: A Review

Abstract: Curcumin (diferuloyl methane), a small-molecular weight compound isolated from the roots of Curcuma longa L. (family Zingiberaceae), has been used traditionally for centuries in Asia for medicinal, culinary and other purposes. A large number of in vitro and in vivo studies in both animals and man have indicated that curcumin has strong antioxidant, anti-carcinogenic, anti-inflammatory, anti-angiogenic, antispasmodic, antimicrobial, anti-parasitic and other activities. The mechanisms of some of these actions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 116 publications
(122 reference statements)
2
59
0
4
Order By: Relevance
“…Curcumin protects the brain from lipid peroxidation and serves as a free radical scavenger and an antioxidant [64][65][66][67][68][69][70]. In addition, curcumin has long been known to possess anti-inflammatory and anti-carcinogenic activities [71][72][73][74]. It has been suggested that the chemopreventive activity of curcumin might be attributed to its ability to induce apoptosis [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin protects the brain from lipid peroxidation and serves as a free radical scavenger and an antioxidant [64][65][66][67][68][69][70]. In addition, curcumin has long been known to possess anti-inflammatory and anti-carcinogenic activities [71][72][73][74]. It has been suggested that the chemopreventive activity of curcumin might be attributed to its ability to induce apoptosis [75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that curcumin has a strong capability for scavenging superoxide radicals, hydrogen peroxide and nitric oxide (NO) from activated macrophages, reducing iron complex and inhibiting lipid peroxidation (Ali et al, 2006;Gowda et al, 2009;Yarru et al, 2009). Curcumin is known to augment antioxidant status especially through SOD which could be due to the increased expression of SOD gene in the chickens fed Turmeric (Cheng et al, 2005).…”
Section: Antioxidant Effectsmentioning
confidence: 97%
“…Turmeric is considered to have low toxicity as revealed in human and animals trials (Ali et al, 2006). There are no reports of adverse effects of either Turmeric or its analogue, except in rare cases.…”
Section: Toxicological Effectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Curcumin possesses a high antioxidant capacity by quenching free radicals generated as a result of various environmental insults and hence its therapeutic effects for either primary prevention or treatment of several human diseases (Ali et al, 2006;Esatbeyoglu et al, 2012). We have recently demonstrated that curcumin has an in vivo protective effect against DEP-induced cardiopulmonary adverse effects in mice (Nemmar et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%